THE IMPORTANCE OF DIDACTIC TASKS IN FORMING THE READING COMPREHENSION SKILLS OF PRIMARY STUDENTS (World Bulletin of Social Sciences, 2025)
This article describes the importance of formation by didactic assignments in the development of understanding students.